Effectiveness of Islamic Spiritual Extracurricular Activities in Shaping Vocational Students’ Character - Devi Puja Kesuma; Asnil Aidah Ritonga (International Journal of Multidisciplinary Research of Higher Education, 2026)
The formation of Islamic character in vocational high schools is an urgent necessity in the face of modernization that often erodes moral and spiritual values among students. Islamic Spiritual extracurricular activities serve as a strategic medium to instill discipline, responsibility, social concern, religiosity, and noble morality. This study analyzes the effectiveness of these activities in shaping students’ Islamic character, drawing upon the perspectives of Lickona, Al-Ghazali, and the Ministry of National Education. Using a qualitative case study design, data were collected through observation, in-depth interviews, and documentation involving students, mentors, and school authorities. Data were analyzed with Miles and Huberman’s interactive model to ensure validity and systematic interpretation. The findings demonstrate that Islamic Spiritual extracurricular activities effectively strengthen students’ Islamic character, particularly in discipline, responsibility, social awareness, religiosity, and morality. Supporting factors include school support, mentor competence, and student enthusiasm, while inhibiting factors involve limited time, external environmental influences, and inconsistent practice at home. The implication highlights the importance of structured and continuous character-building programs to ensure the internalization of Islamic values in daily life. The novelty lies in affirming the direct relationship between extracurricular effectiveness and Islamic character formation, while uncovering gaps between participation and value application outside school.